2021
DOI: 10.3390/jpm11111208
|View full text |Cite
|
Sign up to set email alerts
|

Academic Expectations of Stress Inventory: A Psychometric Evaluation of Validity and Reliability of the Persian Version

Abstract: This study aims to evaluate the psychometric properties of the Academic Expectations of Stress Inventory (AESI) in terms of validity and reliability measurements among Persian students. A total sample of 620 high-school students (nfemale = 328, nmale = 292) was recruited to complete scales on academic expectations of stress, self-efficacy, and depression. The AESI was translated from English to Persian and its translation was further checked by three experts. We used a cross-sectional research design to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…In studies on the sources of stress among youths, Jaramillo et al (2005); Stevenson and Harper (2006); Bhargava and Trivedi (2018) point out that the individual's view influences whether the stressor has a damaging effect or not, and whether it causes physical or psychological symptoms of stress in the individual. Fairbrother and Warn (2003) stated that students may feel several stages of academic stress because they practice different coping practices to manage academic stress (Asgarabad et al, 2021). This may be the rationale why the negative outcomes might come about in physiological reactions or behavioral reactions if a student is incompetent to effectively manage academic stress.…”
Section: Literature Review Academic Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies on the sources of stress among youths, Jaramillo et al (2005); Stevenson and Harper (2006); Bhargava and Trivedi (2018) point out that the individual's view influences whether the stressor has a damaging effect or not, and whether it causes physical or psychological symptoms of stress in the individual. Fairbrother and Warn (2003) stated that students may feel several stages of academic stress because they practice different coping practices to manage academic stress (Asgarabad et al, 2021). This may be the rationale why the negative outcomes might come about in physiological reactions or behavioral reactions if a student is incompetent to effectively manage academic stress.…”
Section: Literature Review Academic Stressmentioning
confidence: 99%
“…Hence, before it results in negative outcomes, it is essential to identify some of the significant or possible causes of academic stress among adolescents. In addition, academic stress was also discovered to have a direct damaging influence on students' self-esteem and dropout rates (Fenzel, 2000;Liu & Lu, 2011;Asgarabad et al, 2021). Parents' high expectations were one of the main sources of adolescents' academic stress, which has been demonstrated to be negatively correlated with their self-esteem.…”
Section: Literature Review Academic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic stress is a rapidly growing phenomenon that in uences students globally (Asgarabad et al, 2021). Evidence showed that rst year nursing students had higher depression rate than fourth year nursing students and by the time they start clinical practice (Janatolmakan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the main cause of academic stress are academic track, admissions, students forced to change/ transfer of admission, exams, burden of extra classes, social comparison, exams stress, teachers and parents expectations (Asgarabad, et al, 2021). It includes the accurate load of learning as well as the physical and mental strain that results from students having to accomplish their tasks, and it contains both subjective and objective components (Long et al, 2013).…”
Section: Introductionmentioning
confidence: 99%